ROLE OF SMECTITE IN SILICEOUS-SINTER FORMATION AND MICROBIAL-TEXTURE PRESERVATION: OCTOPUS SPRING, YELLOWSTONE NATIONAL PARK, WYOMING, USA - Kyle J.E.; Schroeder P.A. (My University, 2007)
A siliceous sinter collected from Octopus Spring in Yellowstone National Park, USA contains an occluded volcanic rock fragment that has undergone alteration. The sinter piece beyond the fragment is mostly dominated by opal-A with trace amounts of bacterial cells, calcite and detrital quartz. Within the altered rock region, the mineral assemblage is dominated by dioctahedral smectite and quartz with trace amounts of pseudobrookite, ilmenite, rutile and hematite. Onset of opal-CT formation was only found in the outer spicular region of the sinter, which is unexpected given that this outer part represents newest growth. A reaction mechanism is proposed whereby the alteration of feldspar to smectitic clay locally produces excess silica, and alkali metal, and raises pH. As the clay mineral forms, it sequesters ions from pore fluids thereby inhibiting the opal-A phase change to more ordered opal-CT. Ions such as Mg are known to promote the opal-A to opal-CT reaction. Smectite formation therefore may assist microbial-texture preservation processes as excess silica produced increases the rate at which primary opal-A is formed. The altered zone also retains the greatest amount of fixed C and fixed N (operationally defined as C and N retained upon combustion at 450°C). The fixed N probably represents ammonium trapped in the exchangeable interlayer site of the smectite. This fixed N may serve as a potential biological signature of microbial activity in ancient rocks formed in similar environments.
Keywords: BIOSIGNATURES; CLAYS; MONTMORILLONITE; NITROGEN; OPAL; PSEUDOBROOKITE; SILICEOUS SINTER; YELLOWSTONE NATIONAL PARK